The Effect of Using a Training Aid on the Development of Performing Summersault front Skill on Still Rings in Artistic Gymnastics for juniors - Majeed, Saleh; Mahmoud, Monther (Journal of Physical Education, 2015)
Chapter One included the introduction and the importance of the study. Gymnastics has been introduced as one of the important and vital individual sports that included different and various methods of training. Training aids to haste learning and performance development and adjustment have also been tackled by the researcher. He shed the lights on gymnastics skills which are (893) and deeply focused on the skills of still rings then tackled the two skills in question as the main important requirement in gymnastics. The problem of the study: There is a lack in the training aids and apparatus that contribute in motor skills learning and development as well as in improving the level of performance and providing safety for gymnasts. Such apparatus may reduce strain done by the coach and the gymnast in the gym especially on the still rings. The difficulty of the rings instability in addition to the difficulty of learning and developing Summersault front Skill make the three steps routine of pulling up the legs, bringing the hips over the shoulder, and pushing the arms down so difficult for beginners. Chapter Two, Literature review and similar studies: This touched a researcher at the Literature review and similar studies Chapter Three, method of study and field procedures: The researcher has used the experimental method as convenient to the nature of the study. The subjects of the study consisted of (8) gymnasts from Baghdad Governorate who were training in Al- Iskan Hall. They have been divided into two groups (control and experimental Chapter Four, display and analysis of results: The (SPSS) was used to extract the results which have been displayed. Chapter Five, conclusions and recommendations: Reach at conclusions and recommendations , Necessity use Training Aid in Artistic Gymnastics for Juniors